Chinese herbal medicine for the treatment of cardiovascular diseases ─ Targeting cardiac ion channels - Zhenzhen Yan; Ling Zhong; Wandi Zhu; Sookja Kim Chung; Panpan Hou (Elsevier, 2023)
Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality, imposing an increasing global health burden. Cardiac ion channels (voltage-gated NaV, CaV, KVs, and others) synergistically shape the cardiac action potential (AP) and control the heartbeat. Dysfunction of these channels, due to genetic mutations, transcriptional or post-translational modifications, may disturb the AP and lead to arrhythmia, a major risk for CVD patients. Although there are five classes of anti-arrhythmic drugs available, they can have varying levels of efficacies and side effects on patients, possibly due to the complex pathogenesis of arrhythmias. As an alternative treatment option, Chinese herbal remedies have shown promise in regulating cardiac ion channels and providing anti-arrhythmic effects. In this review, we first discuss the role of cardiac ion channels in maintaining normal heart function and the pathogenesis of CVD, then summarize the classification of Chinese herbal compounds, and elaborate detailed mechanisms of their efficacy in regulating cardiac ion channels and in alleviating arrhythmia and CVD. We also address current limitations and opportunities for developing new anti-CVD drugs based on Chinese herbal medicines.